1480. Plasma and Urine Pharmacokinetic Analysis of Gepotidacin (GSK2140944) Following BID Oral Dosing in a Phase IIa Study for Treatment of Uncomplicated Urinary Tract Infections - Zimmerman, Eric I (Open Forum Infect Dis, 2019)
BACKGROUND: Uncomplicated urinary tract infections (uUTIs) are very common, with approximately 11% of women >18 years of age experiencing at least 1 episode of acute cystitis per year [Foxman, 2000]. Multidrug resistance has now emerged at the community level and has made treatment approaches for UTIs more difficult [Hooton, 2012; Flamm, 2014; Sanchez, 2016]. Gepotidacin (GEP), a first-in-class, novel triazaacenaphthylene antibacterial has demonstrated in vitro activity against uropathogens, including E. coli. With its unique ability to selectively inhibit bacterial DNA replication by a means not utilized by any currently approved human therapeutic agent, GEP warrants further study as a potential opportunity to address an unmet medical need by providing a new and effective oral treatment option for acute cystitis. METHODS: All participants received oral GEP 1500 mg BID for 5 days (total of 10 doses) and PK sampling was performed on Days 1–5. RESULTS: GEP was rapidly absorbed with median Tmax values of 1.50 to 1.92 hours. Steady-state was attained by Day 3 with moderate accumulation in plasma following BID dosing (1.4 fold), which is consistent with an effective elimination half-life of 6.6 hours. Steady-state urine trough levels were high and remained above an MIC of 4 µg/mL over 12 hours. Approximately 20% of the dose was excreted in urine over the 12-hour dosing interval on Day 1, which increased to 31% on Day 4. Urinary AUC24hr (11945 µg hours/mL) was higher than the free plasma AUC24hr (39.4 µg hours/mL). Slightly higher GEP plasma and urine exposures were observed in uUTI patients compared with Phase I healthy subjects. CONCLUSION: Oral dosing of 1500 mg BID produces urine GEP exposures that exceed free plasma exposures by ~300-fold. Urine concentrations were also higher than the GEP MIC90 values for common UTI pathogens, such as E. coli (MIC90 = 4 µg/mL), suggesting that GEP warrants further clinical study for the treatment of uUTI. [Image: see text] DISCLOSURES: All authors: No reported disclosures.